Exclusive Economic Zone: Contemporary Law of the Sea Fisheries Regulations - Toni, Toni; Kusuma, Winanda; Kurnia, A Cery; Anwar, Muhamad syaiful; sari, Rafiqa (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
The sea as an important area in a country must be able to be maintained both for state sovereignty and respect for sovereign rights. This is regulated in the jurisdiction of the territorial sea regime which applies sovereignty and the EEZ regime which applies sovereign rights. This research analyzes the background of agreements on international regulation of the sea and the utilization of fisheries which are also regulated in international law. The current international law of the sea only strictly regulates regional regimes and territorial jurisdiction, while the nature of fisheries cannot follow this. This research method is normative where international fisheries law arrangements still do not exist. The vacuum of international norms is only filled by weak international agreements and their implementation cannot be forced. The history of the current international law of the sea shows that the basis of the agreement is only related to territory and respect for maritime law in the form of international customs. It needs to be understood that the sea as a natural area must be used in a sustainable manner and also must not violate, so the marine potential, especially fisheries, needs to be agreed with strict sea area regulations and optimal utilization within the framework of the welfare and sustainability of marine ecosystems.